Strategic Blindness in Outer Space: Asymmetric Threat Analysis of Starlink on Indonesia's Cyber Sovereignty and Intelligence Mitigation Strategies - Ridwansyah, Ahmad; Persadha, Pratama Dahlian; Supriadi, Edy (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2026)
The advent of Low Earth Orbit (LEO) satellite constellations, epitomized by SpaceX's Starlink, has fundamentally disrupted the global telecommunications architecture. While offering critical connectivity solutions for archipelagic nations like Indonesia, this technology simultaneously introduces profound asymmetric threats to national security. This study aims to analyze the anatomy of these threats, evaluate their multidimensional impacts, and formulate a comprehensive intelligence strategy to mitigate the hegemony of Starlink's technology. Adopting a post-positivist paradigm, this research utilizes a qualitative descriptive method integrated with the Intelligence Analysis Cycle. The findings indicate that the threat level of Starlink is 'Critical' based on Hank Prunckun's threat matrix (T = I x C), driven predominantly by uncontrolled technical capabilities rather than malicious intent. Starlink is identified as bypassing national gateways, creating